Constraints of Blended Learning Implementation in Higher Education - Hapizah Hapizah; Budi Mulyono; Ely Susanti; Cecep Anwar FS (Jurnal Gantang, 2022)
Blended learning is a combination of synchronous and asynchronous learning. Implementing blended learning in mathematics learning has some problems, one of which is proving mathematics. This study aims to describe the obstacles to implementing blended learning in universities. The research was carried out at two universities in Indonesia located on the islands of Sumatra and Java. The subject of this research is the lecturer of the Mathematics Education Study Program at the two universities. The data collection technique used is an open questionnaire. The data were analyzed qualitatively and descriptively quantitatively. The study's results stated that lecturers faced many obstacles in implementing blended learning, mainly Internet, Time, Competence, and Student Personality.